P-A6 A Possible Role for Retinoic Acid in the Functional cure of SIV Infections in ART/α4β7 mAb-treated Monkeys. (April 2018) - Yu, Jianshi; Jones, Jace; Ansari, Aftab; Sidell, Neil; Kane, Maureen
Abstract : Our team of collaborators has recently reported that combining short term antiretroviral therapy (ART) with the in vivo administration of a primatized monoclonal antibody against the α4β7 integrin (α4β7 mAb) in SIV-infected macaques resulted in sustained control of viremia without need for continued therapy. We have determined that acute SIV infection caused a rapid and sustained drop in plasma retinoic acid (RA) levels that was not corrected upon ART-mediated control of viral replication, but was restored soon after start of α4β7 mAb treatment. This was followed by the rebound of certain CD8α+ NK lymphocytes, cells known to be regulated by RA. Depletion studies of the α4β7 mAb-treated "SIV controllers" with anti-CD8α and anti-CD8β Abs have indicated that rebound of viremia and return to suppression tracks most closely with the depletion and reappearance of NK and NKT cells. In parallel in vitro studies using a cell line model of latent SIV infection (Hut78 and SIV-Hut78), we determined that SIV infection inhibited RA production, while α4β7 mAb treatment can stimulate RA production. The data indicated that SIV-Hut78 cells showed a marked reduction in RALDH2 expression (the key regulatory enzyme in RA biosynthesis). The retinol chaperone protein RBP1 was also reduced in SIV-Hut78 cells. Together, these in vivo and in vitro studies indicate that an increase in RA levels is an early sign of the efficacy of α4β7 mAb treatment and suggests that ligation of the α4β7 integrin leads to intra-cellular signaling events that include the restoration of RA production by select RALDH-expressing cells, and signals that induce NK cell activation/re-distribution that may in concert play a fundamental role in sustained control of viremia.